Large nuclear vacuoles are indicative of abnormal chromatin packaging in human spermatozoa - Franco, J. G. [UNESP]; Mauri, A. L.; Petersen, C. G. [UNESP]; Massaro, F. C.; Silva, L. F. I. [UNESP]; Felipe, V.; Cavagna, M.; Pontes, Anaglória [UNESP]; Baruffi, R. L. R.; Oliveira, J. B. A. [UNESP]; Vagnini, L. D. (Wiley-Blackwell, 2012)
The aim of this investigation was to determine the presence of abnormal sperm chromatin packaging in spermatozoa with large nuclear vacuoles (LNV) selected via high magnification by analysing the pattern of chromomycin A3 (CMA3) staining. A prospective observational study was designed to analyse semen samples obtained from 66 men undergoing infertility diagnosis and treatment. The numbers of cells with normal (dull yellow staining of the sperm head/CMA3-negative) and abnormal (bright yellow fluorescence of the sperm head/CMA3-positive) chromatin packaging were determined on slides with normal and LNV spermatozoa. The presence of bright yellow fluorescence (CMA3-positive) was significantly higher (p < 0.0001) in spermatozoa with LNV than in normal spermatozoa (719/1351; 53.2% vs. 337/835; 40.3%, respectively), reflecting a higher percentage of abnormal chromatin packaging in spermatozoa with large LNV. Our data support the hypothesis that the presence of LNV reflects the presence of abnormal chromatin packaging, which may facilitate sperm DNA damage. As sperm nuclear vacuoles are evaluated more precisely at high magnifications using motile sperm organelle morphology examination (MSOME), the present results support the use of high-magnification sperm selection for intracytoplasmic sperm injection (ICSI).
Keywords: chromatin packaging; chromomycin; chromomycin A3; DNA damage; intracytoplasmic sperm injection; large nuclear vacuoles; motile sperm organelle morphology examination